LEGAL DECISIONS ON THE ACCOUNTING FOR CORPORATE SURPLUS. - Simon, Sidney I. (The Accounting Review, 1956)
Abstract More than six years have passed since the Subcommittee on Terminology of the American Institute of Accountants recommended the discontinuance of the term surplus in accounting. This pronouncement has had considerable effect in accounting circles, and a definite trend away from the use of the condemned term can be perceived. It is true the economic meaning of surplus is different from its accounting signification. To the economist, surplus represents unearned income due to the inelasticity of the supply of any productive factor, conceptually more or less the same as the economic rent of land. The literature of both professions contains many articles comparing the dissimilar meanings of homonymic words common to the two disciplines, so that no student of either should be unduly misled by a different signification of the term surplus in the other profession. Certainly the economist has no greater claim to use of the term than has the accountant. With reference to the problem of the inclusion in capital or paid-in surplus of premium paid on capital stock, the major discussion in the legal decisions revolves around whether such premium on stock is available for dividends, each case interpreting the statute of a particular state.